On the Welfarist Rationale for Relative Poverty Lines - Ravallion, Martin (World Bank, Washington, DC, 2012)
The theory and evidence supporting a relativist approach to poverty measurement are critically reviewed. Various sources of welfare interdependence are identified, including the idea of "relative deprivation" as well other (positive and negative) welfare effects for poor people of belonging to a better-off group. An economic model combines informal risk sharing with the idea of a "positional good," and conditions are derived in which the relative deprivation effect dominates, implying a relative poverty measure. The paper then reviews the problems encountered in testing for welfare effects of relative deprivation and discusses the implications of micro evidence from Malawi. The results are consistent with the emphasis given to absolute level of living in development policy discussions. However, relative deprivation is still evident in the data from this poor but unequal country, and it is likely to become a more important factor as the country develops.